The Next Step?: Suggestions for an Integrative Model for Theorising Ecstasy - Deecke, Moritz (Studia religiologica, 2013)
The article emphasises the necessity of an integral approach for theorising ecstasy and makes a suggestion for how this could be achieved. Although at first it seemed that the compelling sociological theory of ecstasy by I.M. Lewis and the psychological theories by proponents such as Abraham Maslow, Martin Buber or Theresa of Avila contradicted each other and could not both be true at the same time, it now turns out that these two sets of theories have different scopes of application that hardly overlap. They are thus not conflicting, but incommensurable and useful in different contexts. A very elegant and simple model for demonstrating this is the quadrant model by the integral theorist Ken Wilber, as it makes the diverging applicability compellingly visual. Adapting it for the academic study of ecstasy, it can thus be understood that, while sociological theories apply mostly to the occurrence of ecstasy in hierarchical societies among individuals who identify strongly with their group bespeaking their socio-material desires, psychological theories are best employed with individuals who do not strongly identify with group norms and whose ecstatic states cannot be connected with upward social mobility or means to acquire material gain.